The hidden matrix : women's positions and gender relations in Adibasi societies - Chakraborty, Eshani; Ayub Ali, Md. (Dhaka : Pathak Shamabesh, 2009)
On the socio-economic position of rural adivasi women in various Bangladesh districts; a study.
Includes bibliographical references (p. [157]-158) and index.
Keywords: Rural women -- Bangladesh -- Social conditions; Rural women -- Bangladesh -- Economic conditions; Women, Adivasi -- Bangladesh -- Social conditions; Women, Adivasi -- Bangladesh -- Economic conditions